solve for x
asked Jan 22, 2012 in Algebra 1 Answers by anonymous

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:

To avoid this verification in future, please log in or register.

1 Answer

(8 / (x - 2)) - (13 / 2) = (3 / (2x - 4))
(16 / 2(x - 2)) - (13(x - 2) / 2(x - 2)) = (3 / 2(x - 2))
16 - 13(x - 2) = 3
16 - 13x + 26 = 3
-13x + 16 + 26 = 3
-13x + 42 = 3
-13x = 3 - 42
-13x = -39
x = -39 / -13
x = 3
answered Jan 22, 2012 by anonymous

Related questions

1 answer
asked Jun 4, 2014 in Algebra 2 Answers by anonymous | 51 views
1 answer
asked Aug 9, 2012 in Algebra 1 Answers by anonymous | 202 views
1 answer
asked Jun 21, 2012 in Algebra 1 Answers by anonymous | 95 views
1 answer
asked May 8, 2012 in order of operations by anonymous | 110 views
3 answers
asked Nov 3, 2011 in Pre-Algebra Answers by anonymous | 239 views
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
77,100 questions
80,523 answers
1,617 comments
58,769 users